Postoperative complications after removal of pleomorphic adenoma from the parotid gland: A long-term follow up of 297 patients from 2002 to 2016 and a review of publications. Issue 10 (December 2019) - Bonavolontà, Paola; Dell'Aversana Orabona, Giovanni; Maglitto, Fabio; Abbate, Vincenzo; Committeri, Umberto; Salzano, Giovanni; Improta, Giovanni; Iaconetta, Giorgio; Califano, Luigi
Abstract: Pleomorphic adenomas are rounded, lumpy, capsulated lesions that are more common in women. They are typically benign, but can be associated with malignancy in a minority of cases (such as carcinoma ex pleomorphic adenoma), between 3% - 12% of the time, according to available data. The purpose of our study was to evaluate clinical outcomes in patients with benign parotid gland tumours after extracapsular dissection (ECD) or superficial parotidectomy (SP). We made a retrospective study of 297 patients who had had benign tumours of the parotid gland, and had been referred to our department from 2002 – 2016 to have either procedure. We measured the statistical differences between the two techniques (evaluated recurrence rate and complications) with the chi squared test. The chosen level of statistical significance was p < 0.05. Median (range) follow-up time was 43 months (25–168) months. Haematoma and hypoaesthesia were significantly more common after SP than after ECD (8.9% compared with 7.7%, and 16.8% compared with 5.6%, respectively). Transient facial nerve injury, Frey syndrome, and facial paralysis were significantly more common after SP than after ECD (23.6% compared with 1.5%, 6.7% compared with 1% and 6, 7% compared with 0%, respectively). ECD had the advantage of reduced operating time, lower morbidity and lower recurrence rate, and could be considered the treatment of choice for pleomorphic adenoma of the parotid gland up (to 3 cm) which are mobile and sited in the superficial lobe of the parotid gland.